Mine blast algorithm for optimization of truss structures with discrete variables - Sadollah, Ali; Bahreininejad, A.; Eskandar, Hadi; Abd Shukor, Mohd Hamdi (2012)
In this study a novel optimization method is presented, the so called mine blast algorithm (MBA). The fundamental concepts and ideas of MBA are derived from the explosion of mine bombs in real world. The efficiency of the proposed optimizer is tested via the optimization of several truss structures with discrete variables and its performance is compared with several well-known metaheuristic algorithms. The results show that MBA is able to provide faster convergence rate and also manages to achieve better optimal solutions compared to other efficient optimizers. (C) 2012 Elsevier Ltd. All rights reserved.